Global Miljøstyring av Olje- og Gassaktiviteter i Arktis: et institusjonalisert samarbeid eller en uformell dialog? - Refsnes, Aase (Politik, 2011)
Multi-stakeholder cooperation, with focus on private business entities, is receiving increasing attention in the governance literature. Lately, we are witnessing the consequences of global warming; large areas in the Arctic are becoming ice-free, opening for oil and gas activities. This development requires answers to how we should govern these activities in a vulnerable Arctic environment. In a myriad of multi-stakeholder relationships, institutionalized relationships between private and public actors have been prevalent. Consequently, should we expect to witness formal cooperative arrangements between the oil and gas industry, as business representatives, and the Arctic Council, as a representative for the public authorities? Or has global governance theory exaggerated the extent of multi-stakeholder cooperation? Surprisingly, a formal cooperation among the actors does not appear to exist. However there is a high presence of informal cooperation. The question remains; has there been a too narrow focus on the different forms of collaborative action?